Development of Differentiated Learning Tools in Mathematics Learning in Elementary School - Maizuha, Dwi Putri; Nida Jarmita (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
The implementation of differentiated instruction remains ineffective due to learning materials that are overly complex and fail to fully address students' diverse learning needs. This study aims to develop differentiated instructional materials for mathematics learning in elementary schools (SD/MI). The participants of this research consisted of six lecturers serving as expert validators (two material experts, two language experts, and two media experts), one mathematics teacher, and 26 fourth-grade students (Class IV-1) at MIN 8 Aceh Besar. This research utilized the 4-D development model consisting of four stages: defining, designing, developing, and disseminating. Data were collected through observation, expert validation forms, and practicality questionnaires. The data were analyzed using quantitative techniques to assess the feasibility and practicality of the developed instructional materials. The results indicated that the instructional materials were highly feasible. Validation scores were 92.5% from media experts, 89.53% from material experts, and 82.5% from language experts, all categorized as “very feasible.” Additionally, practicality scores were 95% from the teachers and 87.66% from the students, both were categorized as “very practical”. The developed instructional materials are capable of accommodating students' diverse learning styles and are equipped with a digital barcode to facilitate access. There fore these instructional materials are considered valid and practical for use in the learning process.